2022
DOI: 10.7759/cureus.22154
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Mixed Connective Tissue Disorder Involving Bilateral Diaphragm

Abstract: Pulmonary manifestations can be present in 20-80% of patients having mixed connective tissue disorder (MCTD) and are usually subacute. MCTD when associated with polymyositis can rarely involve the diaphragm, causing respiratory failure.We present herein the case of a 49-year-old female having MCTD with a component of polymyositis who presented with bilateral diaphragmatic paralysis followed by heart failure requiring respiratory support with non-invasive mechanical ventilation. We are aware of only one prior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Earlier studies have identified several disorders as possible causes of diaphragmatic dysfunction, such as neuromuscular diseases [56], stroke with hemiplegia [38,57], prolonged artificial ventilation [25,43], damage to the phrenic nerve, disuse atrophy, drugs, infectious or inflammatory conditions, chronic obstructive pulmonary disease (COPD) and hyperinflation [58], systemic lupus erythematosus [59,60], mixed connective tissue disease [61], but, so far, there is little evidence regarding diaphragm function in SSc patients, and further prospective and randomized studies should be encouraged. In our study, there was a wide age range among participants, considering that SSc is a rare orphan disease.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have identified several disorders as possible causes of diaphragmatic dysfunction, such as neuromuscular diseases [56], stroke with hemiplegia [38,57], prolonged artificial ventilation [25,43], damage to the phrenic nerve, disuse atrophy, drugs, infectious or inflammatory conditions, chronic obstructive pulmonary disease (COPD) and hyperinflation [58], systemic lupus erythematosus [59,60], mixed connective tissue disease [61], but, so far, there is little evidence regarding diaphragm function in SSc patients, and further prospective and randomized studies should be encouraged. In our study, there was a wide age range among participants, considering that SSc is a rare orphan disease.…”
Section: Discussionmentioning
confidence: 99%